Blends of acetic acid-modified epoxidized natural rubber with poly(ethylene oxide) / Ng Jin Guan - Ng, Jin Guan (2013)
This dissertation describes a study of using acetic acid to modify epoxidized natural rubber with 50% epoxidation level (ENR50) to form acetic acid-modified ENR50 which was blended with poly(ethylene oxide) (PEO). The study is divided into two sections: (i) Synthesis of modified ENR50 and (ii) Compatibility study on polymer blends comprising of acetic acid-modified ENR50 and PEO. In the first section, ENR50 was dissolved in toluene and reacted with acetic acid. Acetic acid-modified ENR50 formed was precipitated in methanol. Fourier-transform infrared (FTIR) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy were used to investigate the chemical structure while thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to study the thermal properties. Presence of ester and hydroxyl functional groups in acetic acid-modified ENR50 was confirmed. Acetic acidmodified ENR50 possess a higher glass transition temperature (Tg) at 10 oC as compared to ENR50 with Tg at -29 oC. Reaction of 1 mol% of epoxy group leads to an increase in Tg by 0.8 oC. Polymer blends comprising of acetic acid-modified ENR50 and PEO were prepared by solution casting method. Incompatibility of acetic acid-modified ENR50 and PEO is revealed using FTIR analysis. No significant shifting of the major bands observed and there are no obvious changes on the shape of the major bands in FTIR spectra. Tg analysis by DSC shows that acetic acid-modified ENR50/PEO blends are immiscible. Radial growth rate (G) of PEO in acetic acid-modified ENR50/PEO blends decrease with ascending acetic acid-modified ENR50 content and lower G values were observed for acetic acid-modified ENR50/PEO blends compared to ENR50/PEO blends. The fine fibrillar texture of PEO becomes slightly irregular and coarse in acetic acid-modified ENR50/PEO blends. ENR50/PEO blends doped with 12 wt % lithium perchlorate (LiClO4) exhibit ionic conductivities in the range of 10-7 to 10-5 S cm-1 at 30 °C. Acetic acid-modified ENR50/PEO blends with same amount of lithium salt show improved conductivity measurements in the range of 10-6 to 10-4 S cm-1 at 30 oC.